Chloride Adsorption on EDTA Intercalated MnFe-LDHs: Characterization, Performance, and Application - Xue Han (Advances in Materials Science and Engineering)
Ethylenediamine tetraacetate-intercalated Fe-Mn layered double hydroxides (MnFe-EDTA-LDHs) were prepared by coprecipitation. The influence of different factors on Cl− adsorption by MnFe-EDTA-LDHs was investigated. Additionally, MnFe-EDTA-LDHs were incorporated into the concrete to study the Cl− erosion properties. The result showed that the Cl− adsorption on MnFe-EDTA-LDHs was affected by the initial pH, dosage, and coexisting anions. The Cl− adsorption process by MnFe-EDTA-LDHs accorded with the pseudo-second-order model and the Redlich–Peterson model. The maximum adsorption capacity of Cl− on MnFe-EDTA-LDHs reached 129.50 mg/g. The adsorption mechanism involved the complexation of O-containing groups, ion exchange, and electrostatic interaction. Moderate additions of MnFe-EDTA-LDHs improved the resistance of the concrete to Cl− erosion, while excessive additions reduced the Cl− erosion resistance. This work indicated that MnFe-EDTA-LDHs effectively retarded the Cl− erosion on concrete.